The Russian Civil War
XVII, 217 p.
Keywords: Russia's experiences during the Civil War determined the framework within which the Russian people were governed throughout the Soviet period. These newly released documents reveal how the events of 1918-22 reflected struggles and tensions in Russian society that were more complex than the simple Red-White propaganda war. In this collection the authors have sought out documents which highlight the complexities of the struggle, exploring episodes which shed light on what was a multifaceted struggle which left wounds on Russian society which never healed.